Blasting Vibration Law and Prediction in the Near-Field of Tunnel - Meng Wang; Weijie Ding; Dakai Zhao; Dianshu Liu; Lukai Wang; Tao Zhang; Tianlong Ling (Shock and Vibration)
The stability of surrounding rock near the tunnel face is very important to the safety of constructors and the tunnel itself. The vibration law of surrounding rock obtained from the vibration data in the far-field of tunnel blasting is not suitable for the near-field. Therefore, in order to guarantee the safety of tunnel drilling and blasting, it is important to study the vibration law of surrounding rock near the tunnel face. Taking Zhaitang Tunnel, the New Line Expressway of China National Highway 109, as the engineering background, acceleration sensors were installed in the surrounding rock near the tunnel face to test the blasting vibration acceleration of the surrounding rock at the arch waist of the tunnel, to study the blasting vibration attenuation law near the large section tunnel, to modify traditional blasting vibration formula, and to improve the vibration prediction accuracy. The research will bring some guidance for the construction of similar projects.